Perlindungan Hukum terhadap Korban Tindak Pidana Peretasan (Hacking) Berkaitan dengan Pencurian Data - Hidayatullah, Tri Andika; Ismansyah, Ismansyah; Mulyati, Nani (Universitas Ekasakti, 2023)
Hacking is used for other purposes that are detrimental. Legal protection for hacking is regulated in Law Number 19 of 2016. Problem Formulation What is the legal action taken by law enforcers regarding the eradication of criminal acts related to data theft? What is the legal protection for victims of hacking crimes related to data theft? What obstacles do law enforcers encounter in legal protection for victims of hacking crimes related to data theft? Type of research Normative legal research is supported by interviews. Data sources include primary data and secondary data. Data collection techniques are document studies and interviews. Data were analyzed descriptive-analytical. Conclusion of the research results: Law enforcement against hacking or hacking still does not reflect effective law enforcement due to a lack of understanding by investigators. Legal protection is divided into two kinds of preventive legal protection and repressive legal protection. Obstacles encountered by law enforcers in protection law against victims of criminal acts of hacking related to data theft, consists of several aspects, namely: investigator aspects, aspects of evidence in the investigation process, aspects of facilities, aspects of jurisdiction